Leveraging complex network theory to enhance IoT applications in airport management - Alsaeed, Murtaja Natiq Faris; Fard, Kheirolah Rahsepar (Edelweiss Applied Science and Technology, 2024)
The tremendous growth in air traffic and passengers has made airports busier than ever before. This change requires airports to become smarter, more responsive and more efficient to create a seamless airport experience. Airports are increasingly adopting a variety of digital technologies to manage and improve airport performance in terms of resource consumption, carbon emissions and overall passenger journey quality. This graduation project explores the concepts of smart airports and Internet of Things (IoT) technologies. The main objective of the project is to study specific technologies that will have a strong impact on the development of smart airports. The Internet of Things (IoT) technology forms the basis of this project as we believe it is the core technology behind smart airports. By connecting physical assets, equipment, people and applications, IoT plays a vital role in increasing operational efficiency, improving the passenger experience and creating new revenue streams for airports. The project also focuses on the role of specific digital technologies such as blockchain, biometrics, indoor positioning systems, cloud computing and big data in smart airports. The research methodology of the project is based on quantitative literature research with a focus on big data analysis, including white papers, articles, press releases, annual reports and various studies.